Why do general practitioners prescribe antibiotics for acute infective conjunctivitis in children? Qualitative interviews with GPs and a questionnaire survey of parents and teachers. - Rose, P; Ziebland, S; Harnden, A; Mayon-White, R; Mant, D (2006)
BACKGROUND: Acute infective conjunctivitis in children is a common presentation in primary care. Treatment is usually with antibiotics and prescribing may be affected by non-clinical factors. AIMS: To investigate the non-clinical determinants of the management of acute infective conjunctivitis in children. DESIGN: Qualitative interviews with GPs and a questionnaire survey of parents of children with acute infective conjunctivitis and teachers. SETTING: GPs in Sheffield and Berkshire and parents of children with acute infective conjunctivitis and schools in Oxfordshire. METHODS: Semi-structured telephone interviews of 39 GPs. Questionnaire survey of 326 parents of children enrolled into a trial of acute infective conjunctivitis treatment. Questionnaire survey of 223 nurseries and primary schools in Oxfordshire. RESULTS: All three groups agreed that acute infective conjunctivitis was a mild condition. Parents were certain about the benefits of antibiotic treatment and sought early consultations with their GP in a desire to get their child back to school. GPs sometimes collude with a parent's request to prescribe to enable school attendance. Despite this 54.2% (95%CI 48.5-59.8%) children missed a mean of 1.85 days from school and 28.6% of parents (95%CI 23.5-33.7%) missed a mean of 1.5 days off work. CONCLUSION: Social factors, including the need for children to attend day care or school and parents to go to work, contribute to the decision to prescribe antibiotics for children with acute infective conjunctivitis. Understanding these issues and changing school policies in line with national guidance may reduce pressure on GPs to prescribe for this condition.